AUGUSTAN GEOGRAPHY: ONTOLOGICAL PERSPECTIVES - Angelo Turco (Bollettino della Società Geografica Italiana, 2019)
The process of Augustan geography reflects the numerous changes introduced by the Princeps civitatis's reforms. It embeds the cultural, social, political, economic, technological and religious events of the age with varying degrees of speed and stability. At the same time, Augustan geography is a fundamental condition for the paths of transformation that would assail the late Roman world in every field. Imperial geography inaugurated new territorial profiles on the threefold plane of constitutive, configurative and ontological territoriality. This paper focuses specifically on the ontological content of Augustan geography, pivoting around the birth of Jesus Christ. The troubled but unstoppable advent of Christianity introduced new forms of spatial representation, which gradually permeated the Roman world and outlived it. On the one hand, these new representations influenced territorial acts in their material, symbolic and organizational aspects, and on the other, created the perceptions, feelings and emotional conduct that paved the way towards the medieval «appearance» of new configurations of territoriality in Europe and the Renaissance «invention» of landscape.